2022
DOI: 10.1186/s40478-022-01342-7
|View full text |Cite
|
Sign up to set email alerts
|

Microglia phenotypes are associated with subregional patterns of concomitant tau, amyloid-β and α-synuclein pathologies in the hippocampus of patients with Alzheimer’s disease and dementia with Lewy bodies

Abstract: The cellular alterations of the hippocampus lead to memory decline, a shared symptom between Alzheimer’s disease (AD) and dementia with Lewy Bodies (DLB) patients. However, the subregional deterioration pattern of the hippocampus differs between AD and DLB with the CA1 subfield being more severely affected in AD. The activation of microglia, the brain immune cells, could play a role in its selective volume loss. How subregional microglia populations vary within AD or DLB and across these conditions remains poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 115 publications
0
7
0
Order By: Relevance
“…Three decades after the publication of McGeer et al, several groups also used microglial morphological assessment to argue against the initial proposition that microglial activation is a hallmark of LBD neuropathology. Classification of activated microglia by visual confirmation of an ameboid state and increased staining of activation markers, such as CD68, found no increase in activated microglia in LBD brains and, interestingly, the presence of greater numbers of dystrophic microglia compared to age-matched controls [43][44][45][46][47]. A decreased phagocytic capacity of microglia has also been identified in the hippocampus of DLB and PD brains, along with an age-related decline in microglial function in all study groups, including controls [48].…”
Section: Postmortem Investigation Of Microgliamentioning
confidence: 82%
“…Three decades after the publication of McGeer et al, several groups also used microglial morphological assessment to argue against the initial proposition that microglial activation is a hallmark of LBD neuropathology. Classification of activated microglia by visual confirmation of an ameboid state and increased staining of activation markers, such as CD68, found no increase in activated microglia in LBD brains and, interestingly, the presence of greater numbers of dystrophic microglia compared to age-matched controls [43][44][45][46][47]. A decreased phagocytic capacity of microglia has also been identified in the hippocampus of DLB and PD brains, along with an age-related decline in microglial function in all study groups, including controls [48].…”
Section: Postmortem Investigation Of Microgliamentioning
confidence: 82%
“…While such heterogeneity is interesting in relation to the complex structure of the hippocampus and different roles of hippocampal subregions in memory processes, CA1 is one of the earliest sites within the hippocampus to be affected in PD-MCI patients [ 78 , 79 ]. The CA1 is also the most vulnerable subfield in AD, and CA1 microglia was more profoundly affected in AD [ 80 ]. Notably, the microglial production of the pro-inflammatory cytokine TNF-α was largely increased, suggesting that these cells acquired an altered phenotype in response to the infusion of H-αSynOs.…”
Section: Discussionmentioning
confidence: 99%
“…Region-specific variations in gene expression (both increases and decreases) may be implicated in the progression or in the resolution of neurodegenerative diseases [201]. In the hippocampus of AD patients, the subregional pattern of atrophy is different from other groups of neurodegenerative conditions [203,204], and understanding the molecular and cellular mechanisms that lead to such a subregional vulnerability could unveil therapeutic strategies to alleviate the progression of memory decline. Genome-wide association studies (GWAS) identified AD onset risk loci that are associated with genes involved in microglia physiology and responses, such as CR1 (complement receptor type 1), SPI1 (transcription factor PU.1), TREM2 (triggering receptor expressed on myeloid cells 2), and CD33 [205].…”
Section: Microglia Phenomics In Alzheimer's Diseasementioning
confidence: 99%
“…In germ-free (GF) or specific pathogen-free (SPF) mice, the morphology of microglia is severely altered, and the cells have longer, very mobile, hyper-ramified projections (see an example in Figure 1H), which partially overlap in the spatial domains of neighboring microglia [206][207][208] entering into physical contact with the projections of adjacent cells. A possible functional consequence of these alterations of microglia projections is the altered In the hippocampus of AD patients, the subregional pattern of atrophy is different from other groups of neurodegenerative conditions [203,204], and understanding the molecular and cellular mechanisms that lead to such a subregional vulnerability could unveil therapeutic strategies to alleviate the progression of memory decline. Genome-wide association studies (GWAS) identified AD onset risk loci that are associated with genes involved in microglia physiology and responses, such as CR1 (complement receptor type 1), SPI1 (transcription factor PU.1), TREM2 (triggering receptor expressed on myeloid cells 2), and CD33 [205].…”
Section: Dysbiosis and Microgliamentioning
confidence: 99%